State visit by Todor Zhivkov, leader of the Bulgarian Communist Party and government (left) to Angola; right: Angolan president Neto
State visit by Todor Zhivkov, leader of the Bulgarian Communist Party and government (left) to Angola; right: Angolan president Neto.